Book review: Anders af Wåhlberg: Driver Behaviour and Accident Research Methodology; Unresolved Problems - Brookhuis, Karel (European Journal of Transport and Infrastructure Research, 2011)
Anders af Wåhlberg has apparently written this book starting from a negative attitude. He has his own ideas about what is acceptable in traffic psychology research and what is not. Throughout the book he sets his face against the established order such as the rather standard way of using accident statistics, against self-reports, well-known and widely accepted relationships such as exposure and accidents, against traffic conflict studies, and even experimental studies in simulators and instrumented vehicles.